RUSSIA’S POLITICS OF HISTORY - Lopata, Raimundas (Politologija, 2013)
Lithuanian authors have challenges to study Russia’s politics of history. The analysis is complicated because of a few factors. Diplomatic disputes and informative wars between Lithuania and Russia concerning historical questions have encouraged researches by historians but not by political scientists. In Lithuania, the questions of who and how is forming the history politics of Russia, what is its content and the function it accomplishes, remain unexamined. The analysis is further complicated by disagreement among Russian political scientists, historians, journalists, and politicians over the existence of such politics. The present analysis demonstrates that post-soviet Russia perceives the importance of historical memory, i.e. it understands that historical memory and its forms depend on the states’ politics. Russia’s political history genesis testifies that trends of such politics depend on the geopolitical orientation of its government. The end of the Cold War did not manage to conceal the fundamental differences between Europe and Russia. The wave of liberalism and democracy, which spread over Central and Eastern Europe as well as Russian Federation, has caused tension in Russia ruled by B. Yeltsin. Yeltsin’s Russia was not able to tackle this problem by using measures of history politics in order to lessen the distance between Russia and the West. V. Putin undertook to find the solution to this situation, and he did. By using changes of international politics, he builds the image of Russia as a great power. Politics of history are subordinated to build this image; also, it is used as an instrument in domestic politics. The history politics of Russia has taken the shape of a manipulative form and serves the interests of V. Putins’s power.